Designing User Interface & User Experience of Digital Islamic Ecosystem Mobile Application with User Centered Design Method - Ramadhan , Audia Ditsya; Fauzi, Rahmat; Al Anshary, Faishal Mufied (eProceedings of Engineering, 2025)
The globalization era has now entered Industry 4.0 where technology has developed tremendously. In addition to the globalization, the Covid-19 pandemic has forced the entirety of the world to change their whole way of living. In response to these conditions, Muslims must be able to cope with the challenges they face in order to adapt. Digital ecosystem is a solution to the increased numbers of people utilizing their smart phone in their daily activities in this globalization era. Based on the problems stated, the development of an Islamic digital ecosystem application is needed. The UCD is the go-to method for this research because it complies with the objective of the research. The method that will be used for the testing and evaluation of this research is the SEQ and the SUS method. The end result of this research has come up with the solution with the IHYA Digital Ecosystem mobile application, that obtained the result of SEQ testing of average 5, 6, and 7 score and the SUS testing score of 84.2. And it is concluded that the IHYA Digital Ecosystem mobile application design can be easily used and accepted by the users. Keyword — digital ecosystem, muslim, user centered design, system usability scale, single ease question